A Monte Carlo study on dose enhancement and photon contamination production by various nanoparticles in electron mode of a medical linac - Toossi Mohammad Taghi Bahreyni; Ghorbani Mahdi; Sabet Leila Sobhkhiz; Akbari Fateme; Mehrpouyan Mohammad (Nukleonika, 2015)
The aim of this study is the evaluation of electron dose enhancement and photon contamination production by various nanoparticles in the electron mode of a medical linac. MCNPX Monte Carlo code was used for simulation of Siemens Primus linac as well as a phantom and a tumor loaded with nanoparticles. Electron dose enhancement by Au, Ag, I and Fe2O3 nanoparticles of 7, 18 and 30 mg/ml concentrations for 8, 12 and 14 MeV electrons was calculated. The increase in photon contamination due to the presence of the nanoparticles was evaluated as well. The above effects were evaluated for 500 keV and 10 keV energy cut-offs defined for electrons and photons. For 500 keV energy cut-off, there was no significant electron dose enhancement. However, for 10 keV energy cut-off, a maximum electron dose enhancement factor of 1.08 was observed for 30 mg/ml of gold nanoparticles with 8 MeV electrons. An increase in photon contamination due to nanoparticles was also observed which existed mainly inside the tumor. A maximum photon dose increase factor of 1.07 was observed inside the tumor with Au nanoparticles. Nanoparticles can be used for the enhancement of electron dose in the electron mode of a linac. Lower energy electron beams, and nanoparticles with higher atomic number, can be of greater benefit in this field. Photons originating from nanoparticles will increase the photon dose inside the tumor, and will be an additional advantage of the use of nanoparticles in radiotherapy with electron beams.